PENGARUH KUALITAS PELAYANAN, SUKU BUNGA, PROSEDUR KREDIT DAN ASURANSI KREDIT TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PADA PT. BESS FINANCE BOGOR 2 TAHUN 2013-2015 - Rizki Ahmad Fauzi; Adi Hamidi (Jurnal Ilmiah Binaniaga, 2015)
Purpose of this research was to find out whether there is influence of quality of service, interest rates, credit prosedure and credit insurance in credit decision making at PT. Bess Finance Bogor 2, either partially or simultaneously. The research method analyzed using multiple regression analysis. The results showed that for quality of service variable and interest rates variable have a positive influence and significantly of the credit decision making but at credit prosedure variable and credit insurance variable in testing this has no influence significantly in credit making decision. While simultaneously or together quality of service, interest rates, credit prosedure and credit insurance have a positive influence and significantly of the credit decision making at PT. Bess Finance Bogor 2. With coefficient of determination (adjusted R square) in the amount of 0,227 that indicates that amounting to 22,7 % of the credit decision making at PT. Bess Finance Bogor 2 influenced by quality of service, interest rates, credit prosedure and credit insurance, while the rest amounting to 77,3 % of the credit decision making influenced by other variable not examined in this study. Keywords : Credit decision making, of quality of service, interest rates, credit prosedure, credit insurance, partially, simultaneously